Perjumpaan Pendidikan dan Agama: Belajar Hidup Rukun dari Masyarakat Lereng Merapi - Ismanto, Ismanto; Farihah, Irzum (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The main encounter between education and religion is not merely the unity and integrity of the nation and its people, but also the habit of expressing different views among people of different faiths. This study aims to explore the encounter between religion and education in uniting different people in a multi-faith community on the slopes of Mount Merapi. This study uses a micro ethnographic case study approach, with data collected through interviews, observations, documentation, audio-video recordings, and focus group discussions (FGDs). Participants involved in the study include community members such as interfaith leaders, village officials, teachers, community learning center facilitators, farmers, and village residents. The findings of this study indicate that: 1) inclusive education that teaches tolerant values is evident in the interaction between families and the village community to accept and respect each other's different religious beliefs, yet they are given equal opportunities to practice their respective religious teachings; 2) Formal, non-formal, and informal education prioritizes the concept of tepo sliro while maintaining rogo, roso, and tresno in interfaith encounters for the purpose of creating a peaceful and harmonious society; and 3) The religious humanism model with a socio-cultural approach as a model of religious moderation that is practiced in the Lereng Merapi community.